Towards satisfying performance of an O/W cosmetic emulsion: screening of reformulation factors on textural and rheological properties using general experimental design. (14th June 2017) - Filipovic, M.; Lukic, M.; Djordjevic, S.; Krstonosic, V.; Pantelic, I.; Vuleta, G.; Savic, S.
Abstract: Objective: Consumers' demand for improved products' performance, alongside with the obligation of meeting the safety and efficacy goals, presents a key reason for the reformulation, as well as a challenging task for formulators. Any change of the formulation, whether it is wanted – in order to innovate the product (new actives and raw materials) or necessary – due to, for example legislative changes (restriction of ingredients), ingredients market unavailability, new manufacturing equipment, may have a number of consequences, desired or otherwise. The aim of the study was to evaluate the influence of multiple factors – variations of the composition, manufacturing conditions and their interactions, on emulsion textural and rheological characteristics, applying the general experimental factorial design and, subsequently, to establish the approach that could replace, to some extent, certain expensive and time‐consuming tests (e.g. certain sensory analysis), often required, partly or completely, after the reformulation. Methods: An experimental design strategy was utilized to reveal the influence of reformulation factors (addition of new actives, preparation method change) on textural and rheological properties of cosmetic emulsions, especially those linked to certain sensorial attributes, and droplet size. Results: The general experimental factorial design revealed a significant direct effect of each factor, as well as their interaction effects, on certain characteristics of the system and provided some valuable information necessary for fine‐tuning reformulation conditions. Upon addition of STEM‐liposomes, consistency, index of viscosity, firmness and cohesiveness were decreased, as along with certain rheology parameters (elastic and viscous modulus), whereas maximal and minimal apparent viscosities and droplet size were increased. The presence of an emollient (squalene) affected all the investigated parameters in a concentration‐dependent manner. Modification of the preparation method (using Ultra Turrax instead of a propeller stirrer) produced emulsions with higher firmness and maximal apparent viscosity, but led to a decrease in minimal apparent viscosity, hysteresis loop area, all monitored parameters of oscillatory rheology and droplet size. Conclusion: The study showed that the established approach which combines a general experimental design and instrumental, rheological and textural measurements could be appropriate, more objective, repeatable and time and money‐saving step towards developing cosmetic emulsions with satisfying, improved or unchanged, consumer‐acceptable performance during the reformulation.